Development and performance evaluation of a magnetically levitated solar motor - Jamaludin, Azman Bin; Wahid, Mastura Ab; Saputra, Hendri Maja; Yusof, Amy Azlina; Zain, Mohd Zarhamdy Md; Nor, Nur Safwati Mohd (AIP conference proceedings, 2024)
The purpose of developing the magnetically-levitated solar motor is to investigate and evaluate the performance of the solar motor in terms of its efficiency. Magnetic levitation with almost similar applications is being used as test subjects in the study of frictionless support particularly in the design of the vertical axis wind turbine. The current application for support involves mechanical components such as bearing, stator and rotor. By using magnetic levitation, friction can be minimized which eventually contribute to better efficiencies in applications that involve mechanical support and movements. The experiment is more focused on investigating the effects of NdFeB magnet sizes that are used as the rotating base for the motor. Analytical methods by way of theoretical calculations are used to evaluate the results obtained from the experiments. It is then discovered that the efficiency is higher using a bigger size of NdFeB magnet of the same N35 grade. Mass factor also affects the performance of the motor as it can observed that the motor reaches its failure point at lower mass when using bigger size of magnet base as compared to the smaller magnet base. Additionally, there are other factors that were affected by the sizes of the magnet such as the clearance distance (vertical) between the motor and the base, z, and the rotational speed of the motor. The levitated motor design was applied to a solar magnetic fan. Experiment were conducted and the data will be validated and evaluated. The voltage data taken shows a fairly accurate accuracy which is 97.44% of the actual value. The value of RPM also shows the fastest which is 3700rpm. These results also show that the rotation of this fan is faster than the fan that uses USB or battery is as much as 1700rpm available in the market.